English in contemporary Sweden: Perceptions, policies, and narrated practices1. (25th February 2013) - Bolton, Kingsley; Meierkord, Christiane
<x xml:space="preserve">Abstract</x> This paper compares trends in Sweden's language planning and language policies, and particularly the rationale underlying recent government legislation, to actual language use at the 'grass roots' of society, in order to investigate the extent to which academic and official rationales are confirmed by observed language practices. The passing of the Swedish Language Act of 2009 followed debates in academia and the media which not infrequently characterised English as a major threat to the survival of Swedish. However, despite the strong belief in the utility of English widely held in Sweden, the Swedish language is the preferred language of Swedes as well as immigrants in most domains. These results reveal a contradiction between the arguments put forward by a number of academics, educators and journalists concerning the 'threat' of English, and the language practices of ordinary folk in their daily lives.